Ab initio determination of interfacial thermal conductance for polymer-bonded explosive interfaces - Hang Fan; Kun Zhang; Guansong He; Zhijian Yang; Fude Nie (AIP Advances, 2022)
Understanding the thermal transport in polymer-bonded explosives (PBXs) is critical for enhancing the safety and reliability during PBX design, especially in the absence of effective experimental measurements. In this work, we rigorously investigated the phonon properties of 1,3,5-triamino-2,4,6-trinitrobenzene (TATB) and polyvinylidene fluoride (PVDF) and calculated the interfacial thermal conductance using an ab initio approach. The diffuse mismatch model and anharmonic inelastic model were adopted to examine the interfacial thermal conductance as a function of temperature for the TATB–PVDF interface. Our calculation results indicate that low-frequency phonon modes and the two-phonon process play dominant roles in the thermal transport at interfaces. In contrast, high-order phonon processes involving three to eight phonons accounted for around 8% of the interfacial thermal conductance at the TATB–PVDF interface. Phonon properties, such as the velocity and degree of phonon density overlap, are discussed for the TATB–PVDF and 1,3,5,7-tetranitro-1,3,5,7-tetraazacyclooctane (HMX)–PVDF interfaces to estimate the interfacial thermal conductance of PBXs. This study provides a theoretical explanation for the establishment of a research method for PBX thermal transport.